OPTIMALISASI PERAN PENGAWAS MADRASAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DAN SUPERVISI AKADEMIK: STUDI KASUS PADA DIREKTORAT JENDRAL PENDIDIKAN ISLAM KEMENAG PUSAT, JAKARTA - Dina Rahayu Meylasari; Nur Alya Yusra; Syarifah Syarifah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the optimization of the role of madrasah supervisors in improving the quality of learning and academic supervision with a focus on the Directorate General of Islamic Education of the Central Ministry of Religious Affairs. The research uses a case study method based on library research with data sources in the form of scientific journals, books, official policies of the Ministry of Religious Affairs, and relevant academic articles. The results show that madrasah supervisors have a strategic role in coaching, mentoring and evaluating teachers, which has direct implications for improving the quality of learning. Supervisors' professionalism needs to be strengthened not only from technical aspects, but also professional ethics, integrity and moral commitment. Effective academic supervision must be humanist, collaborative and utilize digital technology to be more transparent, fast and have a real impact on teacher competence. On the other hand, policy support and institutional structures from the Central Ministry of Religious Affairs are crucial to ensure the sustainability of the academic supervision program. Thus, this study emphasizes the importance of transforming supervision from merely administrative to continuous professional development for the sake of improving the quality of Islamic education.